(untitled) (Research, Society and Development, 2024)
Introduction: Cranial asymmetries have been increasing over the last few years, especially positional asymmetries, characterized by changes resulting from external forces acting on the baby’s skull, as well as intrauterine movements. Objective: the present study was to identify the average cephalic index (CI) of healthy newborns, aged between 24 and 48 hours of birth, of Brazilian nationality. Methodology: epidemiological study, with a sample of 100 healthy newborns (NB), carried out at the Maternal and Child unit of the Hospital Universitário do Oeste do Paraná (HUOP), between November 11, 2023 and March 20, 2024. interview with mothers and craniometry of newborns. The study was approved by the Ethics Committee: opinion number 5,796,884. Results: The overall mean cephalic index was 81.7% (3.2), for males it was 81.1% (±3.4), and for females it was 82.2% (±3. 0). Conclusion: As a result of the study, it is concluded that for the sample analyzed, the cephalic index (CI) of the newborns was 81.7% (±3.2) and that the score for mesocephaly is 78.5%-84.9%.